SCIENTIFIC SCHOOL «RELIABILITY OF BUILDING STRUCTURES»: NEW RESULTS AND PRESPECTIVES (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article presents the results obtained by scientific school «Reliability of building structures» for the spice of five years2015 – 2019. Some aspects of the general approach to structural reliability assessment have been developed. Currentnormative calculations of structures were combined with the assessment of their reliability. Engineering methods were developed that allow to take into account an increase snow loading on coverage of building of variable height, to estimate theprocesses of snow thawing on roofs of the heated buildings and snow laying on cold roofs. It were investigated the specificwind load in the mountainous Carpathian region and loads of travelling cranes of different producers. Reliability of steelstructures of trunk pipelines and reinforced concrete beams with carbon-fiber reinforcement has been evaluated. Workfeatures of sheet steel structures were investigated. Construction accidents have been analyzed
Keywords: construction; building; structure; reliability; probabilistic method; load